PENINGKATAN HASIL BELAJAR SISWA MENGGUNAKAN TIPE STUDENT TEAMS ACHIEVEMENT DIVISION PEMBELAJARAN IPS SEKOLAH DASAR - Suwandi, Faisal; Marli, Suhardi; Sabri, Tahmid (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractGeneral problem, how to improve student learning outcomes by using Student Teams Achieviement Division in learning IPS class VI SD Negeri 20 South Pontianak?. This study aims to improve students' learning outcomes by using the Student Teams Achieviement DivisionÂ  in Social Science lesson class VI in SD Negeri 20 South Pontianak. The method used is descriptive method with class action research form. This research was conducted in class VI with 3 cycles from one meeting. The result of the research study design (RPP) of cycle I is 3.5., cycle II is 3.75 and, cycle III is 3.97. The results of the implementation of learning from cycle I is 3.25, cycle II is 3.67, and cycle III is 3.86. Result of research result of learning from cycle I that is 63,86, cycle II that is 78,26, and cycle III that is 83,49. So Type Student Teams Achievement Division can improve student learning outcomes of grade VI students of SDN 20 South Pontianak in Social Science.Keyword : Learning outcomes, type Student Teams Achievement Division, and Social Science